Design comparison of surface-mounted permanent magnet synchronous motors with inner and outer rotor configurations - Huu, Hoang Bui; Thanh, Bao Doan; Chuyen, Tran Duc; Quoc, Vuong Dang (Institute of Advanced Engineering and Science, 2024)
The surface-mounted permanent magnet synchronous motor (SPMSM) is one of the electric machines applied widely in the fields of electric vehicles (EVs) and electrical drives due to their good characteristics such as high power density, lower mass, high efficiency, and lower torque. For the SPMSM, there are two types of SPMSM, i.e., the inner rotor SPMSM and the outer rotor SPMSM. To analyze and compute advantages and disadvantages, as well as to compare the performances of these two motor types, this research proposes an analytical model to design preliminarily the main/required parameters of the SPMSM with inner and outer rotor types. Subsequently, a finite element method is developed to simulate, analyze, and compare the electromagnetic parameters of the proposed motors. Via the developed methods, the obtained results will also indicate the performances of both types of motors. In particular, it will provide a good recommendation for choosing the SPMSM with an inner or outer rotor structure for traction applications.